Radiological imaging of pulmonary cavitations in adult multidrug-resistance and extensively drug-resistance tuberculosis patients - Ginting, Justin; Dominika, Katharina Ellen; Sanjaya, Ardo; Gunadi, Julia Windi (Jurnal Prima Medika Sains, 2024)
Mycobacterium tuberculosis is a pathogen that causes the infectious disease tuberculosis. Based on its resistance, tuberculosis can be divided into Drug-susceptible Tuberculosis (DS-TB) and Drug-resistant Tuberculosis (DR-TB). MDR-TB is one type of DR-TB when M. tuberculosis complex strains unresponsive to rifampicin and isoniazid. Another type of DR-TB is XDR-TB, A strain of M. tuberculosis that was unresponsive to rifampicin, isoniazid, fluoroquinolones, and at least 1 drug from group A. Research on the comparison of lung cavities in DS-TB, MDR-TB, and XDR-TB is still limited, this literature review is intended to explore comparative studies of lung cavity radiography in adult MDR-TB and XDR-TB patients. This literature review uses secondary data from literature searches through PubMed and Google Scholar by searching for keywords such as "Pulmonary Cavity", "Multidrug Resistance Tuberculosis", "Extensively Drug Resistance". Articles were included in the inclusion criteria if published in national or international journals with topics that match the research objectives within the last ten years. We found 7 studies that compared the radiologic features of lung cavities in individuals who have been diagnosed with DS-TB, MDR-TB, and XDR-TB. The literature review results showed that the radiologic features of cavities from DR-TB appear to be more massive than those in DS-TB. Similarly, in XDR-TB, the radiological picture of cavities appears more massive than in MDR-TB. The conclusion that can be drawn is that cavitation can be seen in DS-TB and DR-TB, and more cavitation in XDR-TB than in MDR-TB and DS-TB.